Protection through inspection: an exploration of the effectiveness of Irish Inspection Services in relation to promoting a child's right to make a complaint in residential care - Lorraine O'Brien (Scottish Journal of Residential Child Care)
There is a clear understanding by the Irish Inspection Services of appropriate and effective safeguarding practices in relation to young people's right to complain. There are also some areas, however, where the policies and procedures of the inspection services in relation to complaints could be improved. Therefore, consideration is given as to how the effectiveness of Inspection Services could be enhanced.